Optimization of Reaction Condition for Synthesis of 4-Methoxychalcone from Ethyl p-methoxycinnamate - Ismiarni Komala; Muhamad Beny Setiawan; Yardi Yardi (UIN Syarif Hidayatullah Jakarta, 2022)
Ethyl p-methoxycinnamate (1) is the main secondary metabolite found in Kaempferia galanga Linn and has various interesting pharmacological activities, including anti-inflammatory, sedative, vasorelaxant, and antiangiogenic activities. This study aimed to optimize the conditions for the conversion of 1 to 4-methoxychalcone (2) using a conventional synthetic reaction. The conversion was initiated by the hydrolysis of 1 to p-methoxycinnamic acid (3) and 3 to 4-methoxybenzaldehyde (4), and continued with the Claisen-Schmidt reaction of 4 with acetophenone (5). The temperature (room temperature and 45 °C) and ratio of 4 to 5 (1:1 and 1:2) were varied to determine the optimal conditions for the reaction. The results suggested that the reaction of 4 with 5 gave the best yield (42.1 %) when conducted at room temperature in a ratio of 4 to 5 (1:1). The structure of the reaction product was elucidated by spectroscopic analysis and compared with previously published data